Effect of iron oxide addition on the hydration resistance and bulk density of doloma - Yeprem, H. Aygul (ELSEVIER SCI LTD, 2007)
In this study, pure (with no additives) and mill scale (98.66 wt.% Fe2O3 content) added (up to 1.5 wt.%) natural dolomite of Selcuklu-Konya-Turkey fired at 1600-1700 degrees C for 2-6 h using the one-stage process. The resulting bulk densities and apparent porosities of the sintered doloma are investigated. According to the results of experiments with 15 sintered samples, sintering temperature, soaking time and increase of mill scale amount were found to increase the bulk density and thus decrease the observed apparent porosity. In hydration resistance tests, it seemed that the same characteristics also increased the resistance. Furthermore, EDX analysis of the dolomas that were sintered at three different temperatures each with 0.5 wt.% mill scale additions and also at 1700 degrees C/2 h with 0-1 wt.% mill scale additions were performed. Quantities of Fe2+,(3+) inside the periclase (MgO) were examined. Bulk density of pure doloma (CaO.MgO) was calculated using density values of both pure CaO and MgO given in the literature. The difference between the extrapolated value of the measured densities and bulk density of doloma, which is calculated from literature data without porosity is very close. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: dolomite; refractories; sintering; MgO; grain growth; Materials Science